2019
DOI: 10.1101/753905
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of Repeated Treatment with Monoamine-Transporter-Inhibitor Antidepressants on Pain-Related Depression of Intracranial Self-Stimulation in Rats

Abstract: ABSTRACTSynaptic neurotransmission with dopamine (DA), norepinephrine (NE), and serotonin (5-HT) is terminated primarily by reuptake into the presynaptic terminal via the DA, NE, and 5-HT transporters (DAT/NET/SERT, respectively). Monoamine transporter inhibitors constitute one class of drugs used to treat pain, and emergence of analgesic effects by these compounds often requires repeated treatment for days or weeks. The present study compared antinociceptive effects produced b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…The present results agree with our previous finding in rats that repeated daily administration of IP acid can produce both (a) consistent daily episodes of pain-related behavioral depression and (b) weight loss as a potential indicator of depressed feeding (Miller et al, 2015;Legakis et al, 2020). In those previous studies, repeated IP acid decreased a positively reinforced operant-conditioned behavior in rats.…”
Section: Antinociceptive Effects Of Repeated Mjn110supporting
confidence: 93%
See 3 more Smart Citations
“…The present results agree with our previous finding in rats that repeated daily administration of IP acid can produce both (a) consistent daily episodes of pain-related behavioral depression and (b) weight loss as a potential indicator of depressed feeding (Miller et al, 2015;Legakis et al, 2020). In those previous studies, repeated IP acid decreased a positively reinforced operant-conditioned behavior in rats.…”
Section: Antinociceptive Effects Of Repeated Mjn110supporting
confidence: 93%
“…For example, we recently reported that intraperitoneal administration of dilute lactic acid (IP acid) served as an acute visceral noxious stimulus to depress nesting behavior in mice, and this pain-related nesting depression could be significantly but only partially alleviated by MJN110 doses of 0.32-3.2 mg/kg (Diester et al, 2021a;Diester et al, 2021b). Daily IP acid injection produces repeated episodes of behavioral depression and permits assessment of effects produced by repeated drug treatments, and we have shown in rats that morphine-induced alleviation of pain-depressed behavior is resistant to tolerance while effects of some antidepressants increase with repeated administration (Miller et al, 2015;Legakis et al, 2020). The present study used this approach to evaluate antinociception produced by repeated 1.0 mg/kg MJN110 treatment in mice treated with repeated IP acid.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations